Response of different levels of zinc and farmyard manure on growth and yield of pea (Pisum sativum L.) (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted to study the effect of zinc and farm yard manure (FYM) on growth and yield of pea (Pisum sativum L.) during Rabi, 2009-10. The results revealed that application of 40 kg zinc sulphate ha significantly increased vine length at harvest (77.12 cm), number of branches per plant at harvest (5.66), days taken for first flowering (47), number of nodules per plant at harvest (46.28), number of pods per plant (17.22), number of grains per pod, average pod length (cm), average weight of pod (g), weight of grains per green pod (g), shelling percentage (45.61), biomass content (45.86 q ha') and green pod yield (78.95 q ha') over control where no zinc was applied. Similarly, application of FYM at 350 q ha significantly increased vine length at harvest (80.06 cm), number of branches per at harvest (5.79 cm), days taken for first flowering (49), number of nodules per plant at harvest (48.59), number of pods per plant (18.20), number of grains per pod, average pod length (cm), average weight of pod (g), weight of grains per green pod (g), shelling percentage (48.50), biomass content (47.09 q ha') and green pod yield (81.35 q ha") over control where no FYM was applied. The combined effect of zinc (40 kg ha") and FYM (350 q ha') was found significant pertaining to number of branches per plant at harvest (6.15), days to first flowering (51) and green pod yield (80.03 q ha") compared to control and in respect to green pod yield, it was found statistically at par with 0, 150 and 250 qof FYM coupled with 40 kg ha' zinc application.
Keywords: Pea; zinc; FYM; growth; yield; interaction